Geomorphological evidence for ground ice on dwarf planet Ceres - Schmidt, Britney E.; Hughson, Kynan H. G.; Chilton, Heather T.; Chilzon, H. T.; Scully, Jennifer E. C.; Platz, Thomas; Nathues, Andreas; Sizemore, Hanna; Bland, Michael T.; Byrne, Shane; Marchi, Simone; O’Brien, David P. P.; et al. (Nature Geoscience, 2017)
Geomorphological evidence for ground ice on dwarf planet Ceres